2022
DOI: 10.3390/pr10101924
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Temperature and Application Rate of Sugarcane Straw Biochar Influence Sorption and Desorption of Metribuzin and Soil Chemical Properties

Abstract: Pyrolysis temperature and application rate of biochar to soil can influence herbicide behavior and soil fertility. The objective was to investigate the effect of soil amendments with application rates of sugarcane straw biochar, produced at different pyrolysis temperatures, on the sorption–desorption of metribuzin in soil. The analysis was performed using high-performance liquid chromatography (HPLC). The treatments were three pyrolysis temperatures (BC350, BC550 and BC750 °C) and seven application rates (0, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 96 publications
2
15
0
Order By: Relevance
“…Metribuzin presented a greater desorption process than sorption rates, becoming available for absorption and transport processes. This was also found by Mielke et al [ 41 ], although availability is dependent on different biochar rates. Mendes et al [ 33 ] indicate deep profile transport for metribuzin (distributed in 30 cm of soil profile), even with the application of organic material on top of the soil.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Metribuzin presented a greater desorption process than sorption rates, becoming available for absorption and transport processes. This was also found by Mielke et al [ 41 ], although availability is dependent on different biochar rates. Mendes et al [ 33 ] indicate deep profile transport for metribuzin (distributed in 30 cm of soil profile), even with the application of organic material on top of the soil.…”
Section: Discussionsupporting
confidence: 84%
“…Humic substances, from the organic matter degradation portion, have high reactivity, a large surface area, and variable composition, interacting with neutral or ionizable molecules [ 49 , 50 ], such as MTZ formulations. Even stable SOM compounds, which increase hydrophobicity in the soil, can sorb triazines and soluble herbicides such as metribuzin [ 41 , 51 , 52 ]. Therefore, despite the low sorption, soils with consolidated SOM can retain more metribuzin in the soil, in both formulations, reducing the risk of loss.…”
Section: Discussionmentioning
confidence: 99%
“…Herbicide sorption is directly influenced by characteristics such as porosity, SSA, aromatic structures, carbon contents, surface functional groups, pH, and the elemental composition of the soil [ 35 ]. The biochar produced at 750 °C (BC750 °C) showed a higher C/N ratio, ash content, lower number of surface functional groups, and a 13-fold higher surface area than the biochar produced at 350 °C (BC350 °C), which increases the sorption capacity of BC750 °C [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that biochar produced at low temperatures (BC350 °C) negatively influenced the degradation of metribuzin in the soil. The greater degradation of metribuzin in soils amended with BC550 °C and BC750 °C may be related to the physicochemical characteristics of the biochar, as high pyrolysis temperatures produced a material with high pH (9.7), ash content (11%), OC (1.4%), and high nutrient content [ 24 ]. These factors can favor chemical degradation through increased pH, active groups, and generation of free radicals [ 36 ], and the level of C and ash content can affect soil microbial activities due to the presence of nutrient-rich materials (N, S, P, among others).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation